2001
DOI: 10.1046/j.1365-3121.2001.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

No major thermal event on the mid‐Cretaceous Côte d’Ivoire–Ghana Transform Margin

Abstract: Transient mid‐Cretaceous thermal uplift induced by lateral heating from passing oceanic lithosphere is often invoked as a mechanism for the formation of the Côte d’Ivoire–Ghana basement ridge in the Equatorial Atlantic. This heating event should have affected mid‐Cretaceous sedimentary rocks along the ridge. However, organic maturity and clay mineral data on the thermal evolution of these rocks suggest that burial temperatures did not exceed 80 °C and that palaeo–geothermal gradients are not anomalous. Optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…The third explanation is one associated with organic provenance and that the elevated T max values reflect the presence of inert or recycled organic matter and do not reflect the ''true'' thermal maturity of the sampled section. This interpretation was suggested by Wagner and Pletsch (2001). Such an interpretation is consistent with the low production indices for the samples (Fig.…”
Section: Thermal Maturitysupporting
confidence: 87%
“…The third explanation is one associated with organic provenance and that the elevated T max values reflect the presence of inert or recycled organic matter and do not reflect the ''true'' thermal maturity of the sampled section. This interpretation was suggested by Wagner and Pletsch (2001). Such an interpretation is consistent with the low production indices for the samples (Fig.…”
Section: Thermal Maturitysupporting
confidence: 87%
“…Thus by the end of the Albian, the outer Ghana margin was affected by a short but intense thermal pulse, which may have caused thermal uplift of the margin (e.g. Clift & Lorenzo 1999;Sage et al 2000;Wagner & Pletsch 2001). The event is likely to coincide with magmatic underplating observed from deep seismic, gravity and magnetic data across the margin (Antobreh et al 2009;Fig.…”
Section: Uplift and Erosion: Top Syn-rift Unconformitymentioning
confidence: 96%
“…An analytical model for this effect was first developed by Todd & Keen (1989) who demonstrated that, depending on the size of the transform system, the thermal uplift could be up to c. 2 km. The present day position of the marginal ridges and geological and geophysical data have been used to argue that thermal uplift cannot be the cause (Sage et al 2000;Wagner & Pletsch 2001). Other mechanisms have been proposed that focus on the mechanical response, in particular the importance of flexure (Clift & Lorenzo 1999).…”
Section: Introductionmentioning
confidence: 99%
“…OAE II has been causally connected with the opening of the deep-water gateway between the North and South Atlantic that may have allowed the influx of a dense water mass that if volumetrically significant could have displaced nutrient rich deep-waters resulting in rapid ocean overturning and advection of a low N/P ratio water mass to the surface [Arthur and Natland, 1979;Arthur et al, 1987;Kuypers et al, 2002b;Summerhayes, 1987;Tucholke et al, 1979]. A widespread hiatus near the C/T boundary in the late Cenomanian in the South Atlantic [Zimmerman et al, 1987] and Tethys [de Graciansky et al, 1984] may be due to the initiation of this deep-water connection and erosive currents [Wagner and Pletsch, 2001] between the North and South Atlantic and may record this connection. The models of Poulsen et al [2001Poulsen et al [ , 2003 and Handoh et al [1999] demonstrate that the opening of the North-South Atlantic gateway could have been responsible for reorganization of deep-water circulation patterns resulting in introduction of water from the South Atlantic into the North Atlantic basin.…”
Section: C-t Boundary Eventmentioning
confidence: 99%